2012
DOI: 10.1007/s11999-011-2231-1
|View full text |Cite
|
Sign up to set email alerts
|

Capacitive Coupling Reduces Instrumentation-related Infection in Rabbit Spines: A Pilot Study

Abstract: Background Postoperative spine infections cause considerable morbidity. Patients are subjected to long-term antibiotic regimens and may require further surgery. Delivery of electric current through instrumentation can detach biofilm, allowing better antibiotic penetration and assisting in eradicating infection. Question/purposes We asked (1) whether capacitive coupling treatment in combination with a single dose of antibiotics would reduce infection rates when compared with antibiotics alone in a rabbit spine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…showed the efficacy of non-homogenous electric fields (3–4 V/cm) to effectively control the P. aeruginosa and S. aureus growth rate and showed a synergistic effect when applied alongside chloramphenicol treatment [118]. Some studies have also demonstrated the effectiveness of a pulsed electromagnetic field (2000 μA, 1210–7500 V/cm) with increased number of pulses and pulsed electric field that leads to bacterial cell wall disintegration and internal alteration of the core in an in vitro and rabbit spine infection model, which also showed a synergistic effect with the antibiotic ceftriaxone [115, 119, 120, 121]. Studies have also shown the eradication of S. epidermidis , S. aureus and P. aeruginosa biofilms with the use of DC currents (1800 μA) [122, 123].…”
Section: Main Textmentioning
confidence: 99%
“…showed the efficacy of non-homogenous electric fields (3–4 V/cm) to effectively control the P. aeruginosa and S. aureus growth rate and showed a synergistic effect when applied alongside chloramphenicol treatment [118]. Some studies have also demonstrated the effectiveness of a pulsed electromagnetic field (2000 μA, 1210–7500 V/cm) with increased number of pulses and pulsed electric field that leads to bacterial cell wall disintegration and internal alteration of the core in an in vitro and rabbit spine infection model, which also showed a synergistic effect with the antibiotic ceftriaxone [115, 119, 120, 121]. Studies have also shown the eradication of S. epidermidis , S. aureus and P. aeruginosa biofilms with the use of DC currents (1800 μA) [122, 123].…”
Section: Main Textmentioning
confidence: 99%
“…While the use of ES in wound care management is well established, we did not identify any previous studies assessing the impact of ES on wound biofilms in a human ex vivo model. Investigations of ES against biofilms in vivo are also sparse, with only six studies to date having assessed the effect of ES on biofilms, with the majority showing positive outcomes; however, none of these studies investigated the direct effect of ES on cutaneous wound bacterial biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…This could be the result of disruption of the biofilm to release bacteria in the more vulnerable planktonic form or through a molecular or microenvironmental mechanism that is currently unknown. Although there have been numerous in vitro reports on the antimicrobial effects of direct electrical simulation with or without combination with antibiotics [3,6,8,9,17,18,24], there are only a few in vivo reports [7,13,23]. In contrast to the other in vivo models using electrical stimulation to treat implant-associated infections [7,13,23], CVCES uses a three-electrode configuration that allows us to precisely control the cathodic potential of the titanium implant [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been numerous in vitro reports on the antimicrobial effects of direct electrical simulation with or without combination with antibiotics [3,6,8,9,17,18,24], there are only a few in vivo reports [7,13,23]. In contrast to the other in vivo models using electrical stimulation to treat implant-associated infections [7,13,23], CVCES uses a three-electrode configuration that allows us to precisely control the cathodic potential of the titanium implant [10,11]. Although the exact antimicrobial mechanism of CVCES is not well understood, it is believed that cathodic modulation of Ti's voltage-dependent properties is one of the main driving factors for the robust antibacterial effects we have observed in our experiments [10,11,19].…”
Section: Discussionmentioning
confidence: 99%